The Expansion Segments of 28S Ribosomal RNA Extensively Match Human Messenger RNAs - Parker, Michael S.; Balasubramaniam, Ambikaipakan; Sallee, Floyd R.; Parker, Steven L. (Frontiers in Genetics, 2018)
Eukaryote ribosomal RNAs (rRNAs) have expanded in the course of phylogeny by addition of nucleotides in specific insertion areas, the expansion segments. These number about 40 in the larger (25-28S) rRNA (up to 2400 nucleotides), and about 12 in the smaller (18S) rRNA (< 700 nucleotides). Expansion of the larger rRNA shows a clear phylogenetic increase, with a dramatic rise in mammals and especially in hominids. Substantial portions of expansion segments in this RNA are not bound to ribosomal proteins, and may engage extraneous interactants, including messenger RNAs (mRNAs). Studies on the ribosome-mRNA interaction have focused on proteins of the smaller ribosomal subunit, with some examination of 18S rRNA. However, the expansion segments of human 28S rRNA show much higher density and numbers of mRNA matches than those of 18S rRNA, and also a higher density and match numbers than its own core parts. We have studied that with frequent and potentially stable matches containing 7 to 15 nucleotides. The expansion segments of 28S rRNA average more than 50 matches per mRNA even assuming only 5% of their sequence as available for such interaction. Large expansion segments 7, 15 and 27 of 28S rRNA also have copious long (≥10-nucleotide) matches to most human mRNAs, with frequencies much higher than in other 28S rRNA parts. Expansion segments 7 and 27 and especially segment 15 of 28S rRNA show large size increase in mammals compared to other metazoans, which could reflect a gain of function related to interaction with non-ribosomal partners. The 28S rRNA expansion segment 15 shows very high increments in size, guanosine and cytidine nucleotide content and mRNA matching in mammals, and especially in hominids. With these segments (but not with other 28S rRNA or any 18S rRNA expansion segments) the density and number of matches are much higher in 5'-terminal than in 3'-terminal untranslated mRNA regions, which may relate to mRNA mobilization via 5' termini. Matches in the expansion segments 7, 15 and 27 of human 28S rRNA appear as candidates for general interaction with mRNAs, especially those associated with intracellular matrices such as the endoplasmic reticulum.